KEDUDUKAN SAKSI INSTRUMENTER DALAM PEMBUATAN AKTA NOTARIS DALAM HUKUM NASIONAL - HANNA NATHASYA RUMIA HUTAPEA (PREMISE LAW JURNAL, 2016)
A Notary is a public official (openbaar ambtenaar) who has the authority to draw up an authentic deed and other authorities as stipulated in Law No. 2/2014 on Notarial Position. He has to be protected by law, and one of the types of protection is the existence of witnesses who present and directly witness the drawing up of authentic deeds by a Notary; they are called instrumental witnesses. The research used descriptive analytic approach which described in detail and systematically the problems which would be analyzed, based on the description. His responsibility is by witnessing that the person appearing presents before the Notary, the identity of the person appearing has been in line with what has been read by the Notary, the deed is read by the Notary in front of the persons appearing before it is signed, and the deed is signed by the parties concerned and the Notary himself. Keywords: Instrumental Witness, Notarial Deed